The international law on unaccompanied foreign migrant children : an evaluation of whether it reflects the modern realities of economic migrancy in Southern Africa - Skelton, Ann, 1961- (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2014.